1D Supergravity FLRW Model of Starobinsky - Nephtalí E. Martínez-Pérez; Cupatitzio Ramírez-Romero; Víctor M. Vázquez-Báez (Universe, 2021)
We study two homogeneous supersymmetric extensions for the <semantics>f(R)</semantics> modified gravity model of Starobinsky with the FLRW metric. The actions are defined in terms of a superfield <semantics>R</semantics> that contains the FLRW scalar curvature. One model has N = 1 local supersymmetry, and its bosonic sector is the Starobinsky action; the other action has N = 2, its bosonic sector contains, in additional to Starobinsky, a massive scalar field without self-interaction. As expected, the bosonic sectors of these models are consistent with cosmic inflation, as we show by solving numerically the classical dynamics. Inflation is driven by the <semantics>R2</semantics> term during the large curvature regime. In the N = 2 case, the additional scalar field remains in a low energy state during inflation. Further, by means of an additional superfield, we write equivalent tensor-scalar-like actions from which we can give the Hamiltonian formulation.